2016
DOI: 10.3390/toxins8110328
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a LC-ESI-MS/MS Method for the Determination of Alternaria Toxins Alternariol, Alternariol Methyl-Ether and Tentoxin in Tomato and Tomato-Based Products

Abstract: Alternaria species are capable of producing several secondary toxic metabolites in infected plants and in agricultural commodities, which play important roles in food safety. Alternaria alternata turn out to be the most frequent fungal species invading tomatoes. Alternariol (AOH), alternariol monomethyl ether (AME), and tentoxin (TEN) are some of the main Alternaria mycotoxins that can be found as contaminants in food. In this work, an analytical method based on liquid chromatography (LC) tandem mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…In the case of Ginger, even that its essential oils may inhibit fungal growth, some authors reported ginger contamination by mycotoxins specially OTA and AFs [23]. Vegetables like tomato or red fruits have also been reported contaminated by AOH [24,25]. Juan et al [26] also reported AOH in strawberry samples up to 752 µg/kg, amounts similar to those reported in the present study.…”
Section: Mycotoxin Contents In Juicessupporting
confidence: 86%
“…In the case of Ginger, even that its essential oils may inhibit fungal growth, some authors reported ginger contamination by mycotoxins specially OTA and AFs [23]. Vegetables like tomato or red fruits have also been reported contaminated by AOH [24,25]. Juan et al [26] also reported AOH in strawberry samples up to 752 µg/kg, amounts similar to those reported in the present study.…”
Section: Mycotoxin Contents In Juicessupporting
confidence: 86%
“…BEA and ENNs are cyclic depsipeptides, which consist of free electron pairs of oxygen carbonyl groups and tertiary amino groups of amide bonds giving these molecules the ability to act as nucleophiles [8]. Alternaria fungi contaminate a wide variety of food items such as cereals, fruits, wheat, barley, and sorghum, where it produces several toxins, with alternariol (AOH), alternariol-9-methyl ether (AME), and tentoxin (TEN) being the most important ones [9]. Penicillium species are known to produce mycophenolic acid (MPA) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Alternaria mycotoxins were detected in cereals and derived products [46,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76], feed [74,[109][110][111][112][113], dairy products [114], grapes and by-products [27,77,115], tomatoes and derived products [31,47,77,81,106,113], nuts and by-products [102,116], spices [117], soybeans [76,116,118], sunflower seeds [85,104,107], vegetables [27,101], vegetable oils [105], strawberries …”
Section: Prevalence Of Alternaria Mycotoxinsmentioning
confidence: 99%